Two decades of diabetes prevention efforts: A call to innovate and revitalize our approach to lifestyle change. (April 2023) - Golovaty, Ilya; Ritchie, Natalie D.; Tuomilehto, Jaakko; Mohan, Viswanathan; Ali, Mohammed K.; Gregg, Edward W.; Bergman, Michael; Moin, Tannaz
Abstract: The impact of global diabetes prevention efforts has been modest despite the promise of landmark diabetes prevention trials nearly twenty years ago. While national and regional initiatives show potential, challenges remain to adapt large-scale strategies in the real-world that fits individuals and their communities. Additionally, the sedentary lifestyle changes during the COVID-19 pandemic and guidelines that now call for earlier screening (e.g., US Preventative Task Force) will increase the pool of eligible adults worldwide. Thus, a more adaptable, person-centered approach that expands the current toolkit is urgently needed to innovate and revitalize our approach to diabetes prevention. This review identifies key priorities to optimize the population-level delivery of diabetes prevention based on a consensus-based evaluation of the current evidence among experts in global translational programs; key priorities identified include (1) participant eligibility, (2) intervention intensity, (3) delivery components, (4) behavioral economics, (5) technology, and (6) the role of pharmacotherapy. We offer a conceptual framework for a broader, person-centered approach to better address an individual's risk, readiness, barriers, and digital competency.